Pengaruh Profitabilitas, Struktur modal dan Pertumbuhan Perusahaan terhadap Nilai Perusahaan (Studi Pada Bank Perkreditan Rakyat di Kabupaten Buleleng Tahun 2019-2023): Studi pada Bank Perkreditan Rakyat di Kabupaten Buleleng Tahun 2019-2023 - Ni Komang Wina Seftiani; Putu Riesty Masdiantini (Vokasi : Jurnal Riset Akuntansi, 2024)
This research aims to determine the effect of profitability, capital structure and company growth on company value at Rural Banks in Buleleng Regency in 2019-2023. This type of research is quantitative research with descriptive analysis. Data collection is carried out by recording data related to the problem to be studied from documents owned by the company. The type of data used is secondary data obtained from the website www.ojk.ac.id in the form of quarterly financial reports for BPRs in Buleleng Regency for the 2019-2023 period. The population in this research is all BPRs in Buleleng Regency registered with the Financial Services Authority, totaling 8 BPRs. The sample in this study used a saturated sampling technique by taking the entire research population with a sample size of 40 data. The results of this research partially show that; (1) profitability has a positive and significant effect on company value; (2) capital structure has no effect on company value; and (3) company growth has no effect on company value.